Alternative Energies in the Competitive Development of Rural Areas - Inna SOKHAN; Svitlana TERESHCHENKO; Vadym PETROV; Viktoriya VELIEVA; Olga KHLOPOTINA-GNATENKO (Communications of International Proceedings, 2021)
Ukraine has significant unrealized energy saving potential, taking into account natural resources especially in rural areas, where renewable energy sources, should play a leading role. The competitiveness of rural areas is negatively affected by the dominance of energy-intensive energy sources, the deterioration of energy networks of a significant number of agricultural and housing and communal services enterprises and not very modern production technologies. Modernization is therefore an important tool for improving the energy efficiency and competitiveness of rural areas, which is inextricably linked to energy-saving technologies. Given the sharp rise in prices for imported energy for households and entrepreneurs, the introduction of energy efficient technologies is a matter of economic feasibility and ensuring the competitiveness of their own businesses and rural areas in general. The article proved the relevance of the use of alternative energy sources: biomass, solar and wind energy, etc. to ensure the competitiveness of rural development. By applying the method of expert assessments and forecasting, was assessed the state of competitiveness of rural areas in Ukraine and were provided recommendations for sustainable development were provided.
Keywords: Sustainable Development; Rural Communities; Renewable Resources; Solar Energy; Energy Sufficiency; Areas Competitiveness.